Knowledge-sharing strategies in distributed collaborative product development - Sanjay Mathrani; Benjamin Edwards (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Knowledge-sharing strategies are used across the industry as open innovation and distributed collaboration are becoming more popular to achieve technological competencies, faster time-to-market, competitiveness and growth. Sharing of knowledge can provide benefits to manufacturing and new product development (NPD) companies in improving their product quality and enhancing business potential. This paper examines the implementation of knowledge-sharing strategies in New Zealand aimed at bridging the physical locational issues to achieve collaborative benefits in NPD firms through an in-depth case study. The analysis of this only one, but interesting, case extends a holistic multi-mediation model by Pateli and Lioukas for the effect of functional involvement in a distributed collaborative product development environment. This study explores the external and internal knowledge transfer and how it affects early-stage, late-stage, and the overall product development process. Findings present a knowledge-sharing toolset that enhances innovation in all stages of product development overcoming the environmental factors to improve early and late-stage development through a two-way knowledge-transfer loop with distributed stakeholders. An encouraging management culture is found as key for transparent knowledge transfer across cross-functional teams. The organizational structure and management style play an important role for both external and internal distribution of knowledge.
Keywords: 650; open innovation; distributed collaboration; knowledge sharing; knowledge transfer; product development